2022
DOI: 10.1063/5.0102145
|View full text |Cite
|
Sign up to set email alerts
|

A robust and memory-efficient transition state search method for complex energy landscapes

Abstract: Locating transition states is crucial for investigating transition mechanisms in wide-ranging phenomena, from atomistic to macroscale systems. Existing methods, however, can struggle in problems with a large number of degrees of freedom, on-the-fly adaptive remeshing and coarse-graining, and energy landscapes that are locally flat or discontinuous. To resolve these challenges, we introduce a new double-ended method, the Binary-Image Transition State Search (BITSS). It uses just two states that converge to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…To efficiently capture the saddle point, we adopt the binary image transition state search (BITSS) method that has recently been introduced by Avis, et al (Avis et al, 2022). They have also shown that BITSS is more reliable compared to other bracketing methods, where two images are manipulated until they converge to the saddle point.…”
Section: Binary Image Transition State Search (Bitss) Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…To efficiently capture the saddle point, we adopt the binary image transition state search (BITSS) method that has recently been introduced by Avis, et al (Avis et al, 2022). They have also shown that BITSS is more reliable compared to other bracketing methods, where two images are manipulated until they converge to the saddle point.…”
Section: Binary Image Transition State Search (Bitss) Methodsmentioning
confidence: 99%
“…(2.4) is relatively the same to guarantee a successful search. As a result, we keep updating the values of π‘˜π‘˜ 𝑒𝑒 and π‘˜π‘˜ 𝑑𝑑 every three calling of the BITSS energy 𝐸𝐸 𝐡𝐡𝐡𝐡𝑇𝑇𝑆𝑆𝑆𝑆 based on the following formula (Avis et al, 2022)…”
Section: Binary Image Transition State Search (Bitss) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simplest harmonic transition state theory rates are found to agree to within an order of magnitude . LJ 7 2d has also been used to test methods based on reaction coordinates and dimensionality reduction ,, as well as new transition state optimization algorithms …”
Section: The Lennard-jones Potential In Cluster Simulationsmentioning
confidence: 99%
“…409 LJ 7 2d has also been used to test methods based on reaction coordinates and dimensionality reduction 414,418,419 as well as new transition state optimization algorithms. 420 In contrast, calculating interconversion rates between the fcc and incomplete icosahedral morphologies in LJ 38 is significantly harder. The methodology that employs geometry optimization to construct a kinetic transition network 278,286βˆ’288 and then solves the corresponding master equation 421,422 for the dynamics produced quantitative analysis of the rates in 1999.…”
Section: The Lennard-jones Potential In Cluster Simulationsmentioning
confidence: 99%